Health status outcomes after spontaneous coronary artery dissection and comparison with other acute myocardial infarction: The VIRGO experience - Murugiah, Karthik; Chen, Lian; Dreyer, Rachel P.; Bouras, Georgios; Safdar, Basmah; Khera, Rohan; Lu, Yuan; Spatz, Erica S.; Ng, Vivian G.; Gupta, Aakriti; Bueno, Héctor; Tweet, Marysia S.; et al. (PloS one, 2022)
Data on health status outcomes after spontaneous coronary artery dissection (SCAD) are limited. Using the Variation in Recovery: Role of Gender on Outcomes of Young AMI Patients (VIRGO) study we compared patients with SCAD and other acute myocardial infarction (AMI) at presentation (baseline), 1-month, and-12 months using standardized health status instruments. Among 3572 AMI patients ≤ 55 years, 67 had SCAD. SCAD patients were younger (median age (IQR) 45 (40.5-51) years vs. 48 (44-52) in other AMI, p = 0.003), more often female (92.5% vs. 66.6%), have college education (73.1% vs. 51.7%) and household income >$100,000 (43.3% vs. 17.7% (All p<0.001). SCAD patients at baseline had higher mean ± SD Short Form-12 [SF-12] physical component scores [PCS] (48.7±10.2 vs. 43.8±12.1, p<0.001) and mental component scores [MCS] (49.6±12.4 vs. 45.4±12.5, p = 0.008), and at 12-months [PCS (50.1±9.0 vs. 44.3±12.3, p<0.001) and MCS (53±10.1 vs 50.2±11.0, p = 0.045)]. The Euro-Quality of Life Scale [EQ-5D] VAS and EQ-5D index scores were similar at baseline, but higher at 12-months for SCAD (EQ-5D VAS: 82.2±10.2 vs. 72.3±21.0, p<0.001; EQ-5D index scores; 90.2±15.3 vs. 83.7±19.8, p = 0.012). SCAD patients had better baseline Seattle Angina Questionnaire [SAQ] physical limitation (88.8±20.1 vs. 81.2±25.4, p = 0.017). At 12-months SCAD patients had better physical limitation (98.0±8.5 vs. 91.4±18.8, p = 0.007), angina frequency (96.4±8.8 vs. 91.3±16.8, p = 0.018) and quality of life scores (80.7±14.7 vs 72.2±23.2, p = 0.005). Magnitude of change in health status from baseline to 12-months was not statistically different between the groups. After adjustment for time and comorbidities there remained no difference in most health status outcomes. SCAD patients fare marginally better than other AMI patients on most health status instruments and have similar 12-month health status recovery. Better pre-event health status suggests a need to modify exercise prescriptions and cardiac rehabilitation protocols to better assist this physically active population to recover.